(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : The pattern of disease of a community is not always constant. It was observed that every decade produces its own pattern of disease. The pattern of disease depends on the socio-economic factors, as well as historical period, geographical location and other condition. To determine the pattern of disease of soldiers attending at MI room of CMH Ramu. Materials and methods: This descriptive cross-sectional study was conducted at Medical Inspection Room of Combined Military Hospital Ramu, Cox’s Bazar from July 2021 to November 2021. A total of 501 sick soldiers were selected through systematic random sampling for the study. Data were collected by face to face interview with structured questionnaire. Results: Mean age of the respondents was 29.32 ± 1.0 years.Mean age of the respondents was 29.32 ± 1.0 years. Majority of the respondents (53.1%) were in the age group of 20-29 years, followed by 37.1% respondents of 30-39 years. Most frequent acute complaints were fever and injury (100.0%), followed by RTI (97.6%) and musculoskeletal pain (95.7%). Most frequent complaints of chronic disease were hypertension and Diabetes mellitus (100.0%), followed by backache (55.6%), skin disease (11.4%) and eye disease (91.7%).The selected disease like fever, RTI, GI complain, skin disease were higher among the respondents living in the barrack (77.3%) than those who were living in family accommodation (22.7%). Conclusion: The findings of this study revealed that most frequent acute complaints was fever and injury (100.0%), followed by RTI (97.6%), musculoskeletal pain (95.7%). Most frequent complaints of chronic disease were Hypertension and Diabetes mellitus, followed by backache (55.6%), Skin disease (11.4%) and eye disease (91.7%). This study will provide a guideline for planning and implementation of intervention program and resource allocation. It will also provide a guideline for further studies. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 31-35